Investigation of voltage swell mitigation using STATCOM - Razak N.A.A.; Jaafar S.; Hussain I.S. (Institute of Physics Publishing, 2023)
STATCOM is one of the best applications of a self commutated FACTS device to control power quality problems in the distribution system. This project proposed a STATCOM model with voltage control mechanism. DQ transformation was implemented in the controller system to achieve better estimation. Then, the model was used to investigate and analyse voltage swell problem in distribution system. The simulation results show that voltage swell could contaminate distribution network with unwanted harmonic frequencies. Negative sequence frequencies give harmful effects to the network. System connected with proposed STATCOM model illustrates that it could mitigate this problems efficiently. Published under licence by IOP Publishing Ltd.